The Principle Of Binding Force Of A Contract And Its Legal Basis - A Comparative Study - Sherzad aziz sulaiman; Younis Othman Ali (QALAAI ZANIST JOURNAL, 2020)
The principle of the binding force of a contract is one of the most important principles on which the contract is based, whereby the contractor is required to be fully bound by the contract in terms of the content of the contract, which deals with and contains the terms and conditions of the contract. Most comparative civil legislation has confirmed the existence of this principle and considered that the contract is the Law of the parties, i.e. a special law for contractors. Consequently, no party may abstain from the execution of the obligations set forth in the contract and this is not a breach of the contract that entails civil liability, so we have wanted to put this principle in the light of all aspects of this principle, talk about the content of this principle and the position of the legislation on it, and then address the exceptions contained therein, where the law may give one party the power to terminate the contract without the consent of another party and sometimes the judge Authority to amend contract . It is worth mentioning that we have focused on looking for new bases and new ideas for this principle, as there is who believe that the basis of binding force stems from the existence of utility and contractual justice, and there are those who argue that it is trust and legitimate expectations of the creditor that the contract was granted a mandatory element. Through this study, we have found results that the principle of binding force for a contract is a well-established principle of Iraqi and Egyptian civil law, and the recent amendments to the French Civil Code have also confirmed it, which has been established in the Iraqi judiciary as well as in the comparator countries. Whatever the legislator’s role in determining the effects of legal acts, and whatever the impact of social currents on the will to reduce and narrow their capacity, this does not mean eliminating the will to act legally, because in doing so the very doctrine of legal action is eliminated.